A MCM-based microsystem for biological fluids analysis by optical absorption - Minas, Graça (2004)
This paper presents a MCM (Multi-Chip-Module) microsystem for biological fluids analysis. It is composed of three parts: (1) a CMOS silicon optical detection microsystem which includes a photodetector and a light-tofrequency converter for readout; (2) a dielectric thin-film based optical filter on top of the photodetector fabricated using IC-compatible post-processing; (3) a glass die on top containing the microchannels fabricated using SU-8 techniques. The application is in the low-cost measurement of concentration of biomolecules in biological fluids, by the optical absorption in a part of the visible spectrum defined by the specific molecule. Signals proportional to the intensity of the light transmitted through the biological fluid are available at the output in the form of bit streams, which allows simple computer interfacing. The quantitative measurement of total protein in urine is successfully demonstrated. The photodiode responsivity is 224 mA/W with a FWHM (Full-Width-Half-Maximum) of 10 nm at = 600 nm. The optical system sensitivity is 1 kHz/Wm-2 at = 670 nm.